A game theoretic approach to multi-channel transmission scheduling for multiple linear systems under DoS attacks - Zhang, Junhui; Sun, Jitao (Systems & control letters, 2019)
Recent years have illustrated the soaring importance of security issues of cyber-physical systems (CPSs). In this paper, we consider the remote state estimation of a CPS while subject to denial-of-service (DoS) attacks. A number of sensors monitor different linear dynamical systems and transmit the measurements to a remote estimator through a multi-channel network that may suffer corruption due to an intelligent attacker. Both sensors and the attacker have energy constraints. At each time-step, sensors select which channel to transmit over while the attacker chooses which channel to congest. Both sides select strategies based on the current state. In order to model the infinite horizon decision problem, we construct a two player zero-sum game and propose a Nash Q-learning algorithm to solve for the optimal strategies of both players. Finally, simulations are provided to illustrate our results.